Associations between the uptake of 111In-DTPA-trastuzumab, HER2 density and response to trastuzumab (Herceptin) in athymic mice bearing subcutaneous human tumour xenografts. - McLarty, K; Cornelissen, B; Scollard, D; Done, S; Chun, K; Reilly, R (2009)
PURPOSE: The purpose of the study was to investigate the associations between uptake of (111)In-DTPA-trastuzumab, tumour HER2 density and response to trastuzumab (Herceptin) of human breast cancer (BC) xenografts in athymic mice. MATERIALS AND METHODS: The tumour uptake of (111)In-DTPA-trastuzumab in athymic mice bearing BC xenografts with increasing HER2 density (0 to 3+) was evaluated. Specific uptake ratios were established in biodistribution (SUR) and imaging studies (ROI-SUR) using (111)In-labeled mouse IgG ((111)In-DTPA-mIgG). Further corrections were made for circulating radioactivity using tumour-to-blood ratios defined as a localization index (LI) and region-of-interest localization index (ROI-LI), respectively. Mice were treated with trastuzumab (Herceptin). A tumour growth inhibition index (TGI) was calculated and relative TGIs calculated by dividing the TGI of control by that of trastuzumab-treated mice. RESULTS: Strong, nonlinear associations with HER2 density were obtained if the uptake of (111)In-DTPA-trastuzumab was corrected for nonspecific IgG localization (i.e., SUR; r (2) = 0.99) and circulating radioactivity (i.e., LI; r (2) = 0.87), but without these corrections, the association between HER2 density and tumour uptake was poor (r (2) = 0.22). There was a strong association between ROI-SUR and ROI-LI values and HER2 expression (r (2) = 0.90 and r (2) = 0.95, respectively. All tumours were imaged. Relative TGI values were associated with increasing uncorrected tumour uptake of (111)In-DTPA-trastuzumab but not always with HER2 density (i.e., MCF-HER2-18 cells with trastuzumab-resistance). CONCLUSION: HER2 expression (0 to 3+) can be differentiated using (111)In-DTPA-trastuzumab, but requires correction of tumour uptake for nonspecific IgG localization and circulating radioactivity. The uncorrected uptake of (111)In-DTPA-trastuzumab was associated with tumour response to trastuzumab.